Measuring the natural rate of interest in Brazil - Alexis Maka (Institute for Applied Economic Research (ipea), 2023)
This paper applies the Holston-Laubach-Williams methodology to estimate the natural rate of interest for Brazil.
Keywords: E43; E52; C32; 330; natural rate of interest; Kalman filter; trend growth